2016
DOI: 10.1007/s00792-016-0858-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the lipid A from the LPS of the haloalkaliphilic bacterium Halomonas pantelleriensis

Abstract: Halomonas pantelleriensis DSM9661(Τ) is a Gram-negative haloalkaliphilic bacterium isolated from the sand of the volcanic Venus mirror lake, closed to seashore in the Pantelleria Island in the south of Italy. It is able to optimally grow in media containing 3-15 % (w/v) total salt and at pH between 9 and 10. To survive in these harsh conditions, the bacterium has developed several strategies that probably concern the bacteria outer membrane, a barrier regulating the exchange with the environment. In such a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This was also observed in the case of the hexaacylated lipid A from the thermophilic bacterium T. hydrothermalis R‐type LPS, the very short acyl chains of which [namely,11:0(3‐OH) and 11:0] and their symmetric distribution on the glucosamine disaccharide backbone could be responsible for the observed weak immunopotency and the good antagonistic properties towards E. coli LPS toxicity . In contrast, lipid A species acting as agonists on the TLR4/MD‐2 complex, such as those from H. pantelleriensis and A. delamerensis , might also have great potential from a pharmaceutical point of view. As an example, the observation of the preferential induction of one defined type of immune response and not another, as in case of the H. pantelleriensis lipid A, could offer the possibility to use such extremophile lipid A as a starting point for ad hoc synthesized derivatives to employ as immunoadjuvants.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 76%
See 3 more Smart Citations
“…This was also observed in the case of the hexaacylated lipid A from the thermophilic bacterium T. hydrothermalis R‐type LPS, the very short acyl chains of which [namely,11:0(3‐OH) and 11:0] and their symmetric distribution on the glucosamine disaccharide backbone could be responsible for the observed weak immunopotency and the good antagonistic properties towards E. coli LPS toxicity . In contrast, lipid A species acting as agonists on the TLR4/MD‐2 complex, such as those from H. pantelleriensis and A. delamerensis , might also have great potential from a pharmaceutical point of view. As an example, the observation of the preferential induction of one defined type of immune response and not another, as in case of the H. pantelleriensis lipid A, could offer the possibility to use such extremophile lipid A as a starting point for ad hoc synthesized derivatives to employ as immunoadjuvants.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 76%
“…Very recently, Carillo et al have elucidated the H. pantelleriensis lipid A structure (Figure b), showing a family of species differing in the acylation profile with 12:0(3‐OH) units as primary fatty acids and 10:0 and 12:0 units as secondary fatty acids linked to the N ‐acyl residues at positions 2 and 2′ of the glucosamine backbone, respectively. Lipid A species lacking a phosphate group or the primary ester‐linked 12:0(3‐OH) on the reducing glucosamine moiety were also detected (Figure b) . Interestingly, Carillo et al have also observed the capability of H. pantelleriensis lipid A to induce a Th1‐type immune response by triggering the production of IFN‐γ and TNF‐α, whereas the Th2‐type cytokine release IL‐4 and regulatory IL‐10 were only slightly induced.…”
Section: Lps In Gram‐negative Extremophiles: Structural and Biologmentioning
confidence: 91%
See 2 more Smart Citations